2022
DOI: 10.3390/diagnostics12081789
|View full text |Cite
|
Sign up to set email alerts
|

Intratemporal Facial Nerve Schwannomas: A Review of 45 Cases in A Single Center

Abstract: There are no established indications for facial nerve schwannoma treatment, including surgery, radiation and follow-up observation, and it is difficult to determine treatment policy uniformly. The treatment policy was examined from each treatment course. Data of patients with facial nerve schwannomas at our hospital from 1987 to 2018 were retrospectively examined. Their age, sex, clinical symptoms, tumor localization, treatment policies and outcomes were reviewed. In total, 22 patients underwent surgery and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…It should also be noted that a certain percentage of tumors do not grow without intervention. Although several studies have reported treatment timing [8,9 ▪ ], no established standard for treatment selection integrates each perspective.…”
Section: Facial Nerve Schwannomamentioning
confidence: 99%
See 3 more Smart Citations
“…It should also be noted that a certain percentage of tumors do not grow without intervention. Although several studies have reported treatment timing [8,9 ▪ ], no established standard for treatment selection integrates each perspective.…”
Section: Facial Nerve Schwannomamentioning
confidence: 99%
“…If there is no compression of the brain or a tendency for tumor growth, a wait-and-scan approach is a good option. When facial nerve paralysis occurs during follow-up observation, steroids and decompression should be considered to prevent worsening of facial nerve paralysis [9 ▪ ].…”
Section: Facial Nerve Schwannomamentioning
confidence: 99%
See 2 more Smart Citations
“…Virus or bacterial infection is the second most common ethology of palsy like Ramsay Hunt syndrome associated with a varicella zoster infection or Lyme disease associated with the bacterium Borrelia burgdorferi [3,4]. A progressive onset of facial palsy should raise suspicion of malignancy; acoustic or facial nerve neurinoma, meningioma, parotid tumours and schwannoma should be considered [5,6].…”
mentioning
confidence: 99%